Revision of the Holarctic species of Dilyta Förster (Hymenoptera: Figitidae: Charipinae) with descriptions of four new species from the eastern Palaearctic - Paretas-Martínez, Jordi; Ferrer-Suay, Mar; Kovalev, Oleg; Melika, George; Selfa, Jesús; Pujade-Villar, Juli (Zootaxa, 2011)
The genus Dilyta, and the known species of this genus present in the Holarctic, D. subclavata Förster from Europe and D. rathmanae Menke and Evenhuis from USA, are redescribed. Four new species of Dilyta are described from the eastern Palaearctic region: D. aleevae sp. n. from Kazakhstan, D. japonica sp. n. from Japan, and D. longinqua sp. n. and D. sinica sp. n. from China. All six species have an ∩ -shaped carina on the apex of the scutellum; this character differentiates these species from the Afrotropical species, which instead have two small symmetrical and parallel carinae. A key to the species of Dilyta in the Holarctic is provided. Apocharips talitzkii (Belizin) is synonymyzed with D. subclavata.